2012
DOI: 10.5664/jcsm.2024
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Induces Oropharyngeal Narrowing and Increases the Severity of Obstructive Sleep Apnea Syndrome

Abstract: anatomic factor for OSAS. [11][12][13] Pathological conditions such as a redundant or long uvula and enlarged tonsils are thought to be the predominant causes of upper airway collapse during sleep and are indications for surgery to decrease snoring, apnea, and snoring-related cardinal symptoms. The upper airway mucosa can be easily affected by smoking, and longer exposure to smoking may cause abnormal histological changes to the upper airway mucosa. Therefore, evaluation of the uvular changes after exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 35 publications
2
56
1
2
Order By: Relevance
“…This study did not identify smoking as a risk factor to sleep disorders, as oppose to the others 13,14 . In the study of Kim et al 13 , it was observed that smoking may trigger sleep disorders and even be a risk factor to the obstructive sleep apnea syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study did not identify smoking as a risk factor to sleep disorders, as oppose to the others 13,14 . In the study of Kim et al 13 , it was observed that smoking may trigger sleep disorders and even be a risk factor to the obstructive sleep apnea syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Kim et al 13 , it was observed that smoking may trigger sleep disorders and even be a risk factor to the obstructive sleep apnea syndrome. This way, the differences observes between these studies may be explained, at least …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…128 Both OSA and COPD are associated with inflammatory cell activation and hypoxia. 113 These may lead to endothelial dysfunction, and consequently several adverse outcomes.…”
mentioning
confidence: 99%
“…16,17 For instance, in those with existing SDB, alcohol use, or smoking may exacerbate SDB severity by depressing upper airway dilator tone or causing upper airway inflammation, respectively. 18,19 Moreover, exercising, maintaining a regular out-ofbed time, refraining from evening caffeine, and/or minimizing daytime napping could facilitate better sleep quality (e.g., more slow-wave sleep, less fragmentation), which is protective against SDB. 20,21 Because of the possible utility of sleep hygiene education for the behavioral management of insomnia or SDB, determining the frequency of these behaviors could inform future interventions to improve sleep in midlife women.…”
mentioning
confidence: 99%